The Multidimensional Functions of Ashura: A Thematic Analysis from the Perspective of Gastronomy and Social Economy (Third Sector Social Economic Review, 2025)
This study aims to examine the multi-dimensional functions of ashura, centered on gastronomy, within the framework of Social Capital Theory. Although numerous religious, historical, and cultural studies exist, little attention has been paid to evaluating this ritual in terms of social capital generation, solidarity economy, and cultural heritage transmission within the discipline of gastronomy. Based on this gap, the study assumes that ashura is not only a ritual meal but also a cultural element that strengthens social memory and builds connections among different communities. A qualitative approach was adopted, employing literature review and document analysis. The data were evaluated through thematic content analysis, and recurring concepts were coded under four main themes: social, economic, cultural, and symbolic. The findings reveal that ashura strengthens sharing, solidarity, and neighbourly relations in the social dimension; supports local production, agricultural diversity, and the solidarity economy in the economic dimension; represents intangible cultural heritage in the cultural dimension; and conveys layered symbolic meanings such as abundance, unity, and mourning. Overall, the results show that ashura can be regarded as a multi-layered heritage that produces social capital and sustains social memory, offering interdisciplinary contributions and paving the way for future studies on tourism, cultural diplomacy, and sustainability.
Keywords: Ashura; Gastronomy; Social Capital; Solidarity Economy; Intangible Cultural Heritage